2002
DOI: 10.22358/jafs/67829/2002
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic simulation model of nutrient digestion in the rumen of dairy cows

Abstract: A mechanistic model of nutrient digestion in the rumen of dairy cows has been developed to predict rates of nutrient digestion and passage as well as rumen NDF pool sizes at fixed rates of dry matter intake. Different feed fractions according to chemical and physical characteristics are considered. There are 18 rumen state variables representing carbohydrates, nitrogen and microbes in the model. The model is mainly sensitive to the parameters defining rate constants of passage of small particles and digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This short-term adaptation delays the disposal of energy by microbes. Consequently, whereas fractional degradation rates of 150% to 300%/h are assumed for WSC in some rumen models Petruzzi et al, 2002), a much lower fractional degradation is more likely, but experimental evidence is lacking. Satisfactory adjustments are obtained assuming a fractional rate of around 40%/h (D. Sauvant, unpublished).…”
Section: Starchmentioning
confidence: 99%
See 1 more Smart Citation
“…This short-term adaptation delays the disposal of energy by microbes. Consequently, whereas fractional degradation rates of 150% to 300%/h are assumed for WSC in some rumen models Petruzzi et al, 2002), a much lower fractional degradation is more likely, but experimental evidence is lacking. Satisfactory adjustments are obtained assuming a fractional rate of around 40%/h (D. Sauvant, unpublished).…”
Section: Starchmentioning
confidence: 99%
“…Concerning passage rate, two or three outflow rates are generally considered. The liquid and the solid phases are either considered globally , or separated between forage and concentrate particles Lescoat and Sauvant, 1995), or between large and small particles (Baldwin et al, 1987b;Petruzzi et al, 2002). Although most models represent the effect of intake level on flow rates, equations vary widely among models.…”
Section: Carbohydrate Digestion and Nutrient Fluxesmentioning
confidence: 99%
“…(K_EP;0.2856). From the analysis of the rumen model on which the feed intake regulation model is based (see Petruzzi et al, 2002), it was demonstrated that the rumen model was sensitive to parameters defining the rate constant of passage of small particles (KpSP) and the digestion rate constant of NDF. Hence, parameters a (0.01), b (0.052) and d (3.2) were also included in the sensitivity analysis of FIRM.…”
Section: Methodsmentioning
confidence: 99%
“…Decomposition of the mean square prediction error (MSPE) into error due to central tendency (ECT), error due to regression (ER) and error due to disturbance (ED) was done as defined by Bibby and Toutenberg (1977). Significance and formulas to calculate these terms were also presented in Petruzzi et al (2002). The RMSPE expressed as a percentage of the observed mean is used as a measure of the prediction error.…”
Section: Evaluation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation